Constitutively Active TRPC Channels of Adipocytes Confer a Mechanism for Sensing Dietary Fatty Acids and Regulating Adiponectin - Sukumar, Piruthivi; Sedo, Alicia; Li, Jing; Wilson, Lesley A.; OʼRegan, David; Lippiat, Jonathan D.; Porter, Karen E.; Kearney, Mark T.; Ainscough, Justin F.X.; Beech, David J. (Circulation research, 2012)
RATIONALE:Calcium entry is pivotal in the heart and blood vessels, but its significance and mechanisms in adipose tissue are largely unknown. An important factor produced by adipocytes is adiponectin, which confers myocardial protection, insulin-sensitization, and antiatherosclerotic effects. OBJECTIVE:To investigate the relevance of calcium channels to adipocytes and the production of adiponectin. METHODS AND RESULTS:Microarray analysis led to identification of transient receptor potential canonical (TRPC)1 and TRPC5 as channel subunits that are induced when adipocytes mature. Both subunits were found in perivascular fat of patients with atherosclerosis. Intracellular calcium and patch-clamp measurements showed that adipocytes exhibit constitutively active calcium-permeable nonselective cationic channels that depend on TRPC1 and TRPC5. The activity could be enhanced by lanthanum or rosiglitazone, known stimulators of TRPC5 and TRPC5-containing channels. Screening identified lipid modulators of the channels that are relevant to adipose biology. Dietary ω-3 fatty acids (eg, α-linolenic acid) were inhibitory at concentrations that are achieved by ingestion. The adipocyte TRPC1/TRPC5-containing channel was functionally negative for the generation of adiponectin because channel blockade by antibodies, knock-down of TRPC1–TRPC5 in vitro, or conditional disruption of calcium permeability in TRPC5-incorporating channels in vivo increased the generation of adiponectin. The previously recognized capability of α-linolenic acid to stimulate the generation of adiponectin was lost when calcium permeability in the channels was disrupted. CONCLUSIONS:The data suggest that TRPC1 and TRPC5 contribute a constitutively active heteromultimeric channel of adipocytes that negatively regulates adiponectin and through which ω-3 fatty acids enhance the anti-inflammatory adipokine, adiponectin.